Inovasi Pembelajaran Bahasa Inggris: Penerapan Smart Grammatica App untuk Meningkatkan Kualitas Pendidikan di Mosaic Kampung Inggris Pare - Hamidah, Fitria Nur; Sukya, Fadelis; Dion Yanuarmawan; Dja’far, Veri Hardinansyah; Setianingsih, Novie Astuti; Bahtiar, Ahmad Dony Mutiara (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2026)
This community service activity is the activity which gives innovation in English language learning, namely by providing the Smart Grammatica app to improve the education quality at Mosaic Kampung Inggris Pare. The purpose of this community service activity is to disseminate and give knowledge about the use, utilization, and application of the Smart Grammar app as an effective, fantastic, and innovative learning media in English teaching and learning, especially English grammar, at Mosaic Kampung Inggris Pare. The target audience is the English tutors at Mosaic Kampung Inggris Pare. The methods used are approach and implementation methods, which consist of some stages, those are the preliminary, the socialization and audience, and the evaluation also motivation. This activity was done in several stages. The first was the introduction of Smart Grammar app. The next stage was the explanation and practice of utilizing Smart Grammar app in teaching English grammar. The final stage was evaluation and motivation. The outcome of this community service is the English tutors at Mosaic Kampung Inggris Pare are able to utilize, use, and apply Smart Grammar app as the effective, fantastic and innovative English learning and teaching media for teaching English grammar. In addition, this app can serve as motivation and be very popular among learners who are studying English grammar at Mosaic Kampung Inggris Pare.